Seed source impacts germination and early establishment of dominant grasses in prairie restorations. Issue 1 (14th December 2015) - Gallagher, M. Kate; Wagenius, Stuart
Summary: Land managers choose seed from a variety of provenances for restoration projects. By selecting seed of the local ecotype, managers can increase establishment in the short term and prevent the disruption of local adaptations and genetic swamping in the long term. However, local seed may be disadvantageous if populations are inbred or maladapted to managed restoration environments. Seed selection may be further confounded by propagation methods. Three dominant C4 grasses, Andropogon gerardii, Bouteloua curtipendula and Sorghastrum nutans, from three types of seed provenances (remnant, restoration and nursery) were planted as seeds and plugs into experimental plots at three established tallgrass prairie restorations in western Minnesota, USA. Using a common garden design, we tested whether (i) provenance and (ii) site of planting influence germination and first‐season survival and growth both (iii) for seeds directly planted in the field and for transplants (plugs). Seed provenance impacted germination and seedling survival in all cases, except S. nutans seeded directly in the field. Andropogon gerardii and B. curtipendula nursery seedlings were consistently taller than those of the other provenance types. When directly seeded, germination, survival and vigour differed among restoration sites; however, the results were species specific. Sorghastrum nutans germination varied among sites depending on provenance, indicating that this species may be particularly sensitive to environmental conditions. Germination was 3–12 times greater for plugs than for seeds directly planted in the field in summer, but mortality after planting in the field was low for both groups. Synthesis and applications . Provenance and restoration site had varying effects among species, indicating that the dominant C4 grasses used in this study ought not to be considered ecological equivalents. While we found little evidence of local adaptation, use of local remnant seeds diminishes the risk of spreading maladapted genotypes. Germination limited establishment when sowing seeds directly in summer. Supplemental use of plugs may increase species diversity in restorations.